Penilaian Pengertian al-Jawf Menurut Pandangan Fiqh Dan Perubatan Moden - Ab Ghani, Anisah; Mat, Hamidah (Jurnal Fiqh, 2011)
This article is developed with the proposition that the classical literature of fiqh does not give an intensive or detailed definition of al-jawf which justifies fast breaking according to the rulings of fiqh from a scientific point of view. Due to the loose definition of al-jawf adopted by the classical fuqaha (jurists), the treatment of any kind of sickness is often viewed as nullifying fasting. Likewise, the classical unscientific and narrow definition of ?al-jawf? (cavitiy) has also been identified as another element that contributes towards the aforementioned old fiqh paradigm. Thus, this research aims to redefine the term al-jawf in details with its categories based on modern scientific discoveries within the framework of the fiqh rulings concerning fasting. Furthermore, the proposed framework will be applied to the situation of sick patients who observe their fasting during the treatments.